Intussusception in preterm neonates: A systematic review of a rare condition - Mostafa Kotb; Mostafa Abdelatty; Hayssam Rashwan; Yasmine AbdelMeguid; Ahmed Elrouby (BMC, 2021)
Abstract Background While necrotizing enterocolitis (NEC) is a prevalent condition in preterm neonates admitted to neonatal intensive care unit (NICU), intussusception is exceedingly uncommon and often overlooked. This is due to the fact that they share many clinical characteristics. The initial misdiagnosis of intussusception in preterm neonates (IPN) especially has led to a delay in their management, which increases the risk of developing compromised bowel. Additionally, it is difficult to reach a diagnosis as neonatal intussusception does not have any classical radiological signs even when contrast enema is used. This systematic review is based on the published literature including case reports and case series to review the clinical features of IPN and how to differentiate it from NEC in order to shed the light on this rare disease and how having a high index of suspicion would help practitioners to make an early and accurate diagnosis Methods A systematic literature search to report all cases of relevant articles that reported IPN till date. All cases that were born before 37 weeks gestational age, presented within the neonatal period and having well established documentation were included in the study. Any case that did not have these criteria was excluded from our study. Results Only 52 cases met these criteria during the period from 1963 till date. An average of 10 days had elapsed before the cases were confirmed to have IPN either clinically or intraoperatively. The most frequent manifestations were abdominal distension and bilious gastric residuals, occurring in 85% and 77% of the cases respectively, followed by bloody stools in 43% of cases. However, this triad was present only in approximately one-third of the cases. Only 13 cases were diagnosed as having intussusception preoperatively. About two thirds of the intussusception were located in the ileum. Pathological lead point was present in 7 cases only; 4 of them were due to Meckel's diverticulum. Nine cases only out of the 52 cases with IPN died. Conclusion It is crucial to detect the clues for diagnosis of intussusception because in contrast to NEC, it is unresponsive to conservative management, affects the viability of the bowel and surgery is essential.